Judicial Reform Pursuits in Ethiopia, 2002-2015: Steady Concrete Achievements - versus - Promise Fatigue - Stebek, EN (Mizan law review, 2016)
Judicial reform constitutes a sub-program within the Justice System Reform Program (JSRP) which is underway in Ethiopia since 2002. Its targets have been consistently articulated in the 2005 Comprehensive Justice Sector Reform Program, the First Growth and Transformation Plan and various strategic plans. However, the outcome and impact as, inter alia, manifested in public trust and confidence seem to be declining. The core problems in the Ethiopian justice system (including the judiciary) that were identified in the 2005 Comprehensive Justice Sector Reform Program were (a) gaps in accessibility and responsiveness to the needs of the poor, (b) inadequacy of “serious steps to tackle corruption, abuse of power and political interference in the administration of justice,” and (c) inadequate funding which “aggravates most deficiencies of the administration of justice”. As these problems still persist, I argue that future judicial reform pursuits require a new path which facilitates court-level and institution-level reform through grassroots empowerment including enhanced independence and resource allocation. Subject to justice sector reform harmonization, there should be an independent judicial reform which is not conflated with other components of justice sector reform. It is also argued that justice sector reform should not be subsumed under the Good Governance Reform Cluster which should rather be limited to macro-level harmonization of reform pursuits. In the absence of such measures, the various targets, aspirations and pledges for judicial reform may eventually end up in promise fatigue and regression. Key terms: Judicial reform, judiciary, judicial independence, rule of law, GTP, Ethiopia